THE EFFECTIVENESS OF SKIMMING AND SCANNING STRATEGIES IN IMPROVING STUDENTS' READING COMPREHENSION (Multidisciplinary Journal of Science and Technology, 2026)
This article examines how skimming and scanning strategies can improve students’ reading comprehension, especially when learners must handle long texts under time pressure. Skimming supports global understanding by helping readers capture topic, purpose, and main ideas quickly, while scanning enables fast location of specific facts such as names, dates, definitions, and key details. Drawing on established reading scholarship and classroom evidence, the article explains why these strategies work, what conditions make them most effective, and how teachers can train students to use them deliberately rather than randomly. The discussion highlights cognitive benefits such as better allocation of attention, clearer reading goals, and reduced overload during academic tasks.